Effect of Co/Cu partial replacement on fundamental features of Y-123 ceramics - Ozturk, Ozgur; Nefrow, Abdul R. A.; Bulut, Fatih; Ada, Hakan; Turkoz, Mustafa B.; Yildirim, Gurcan (Springer Science and Business Media LLC, 2020)
This study is liable for the effect of sample production processes including the standard solid-state reaction (SSR) and classical sol–gel (SG) preparation methods on the fundamental characteristic features, namely electrical, superconducting, crystal structure quality, crystallinity, morphological, strength quality of grain boundary couplings, and interaction between the grains of YBa2Cu3−xCoxO7−δ (Y-123) advanced ceramic compounds within the weight ratio intervals x = 0–20%. The main heat treatments are exerted at two main steps: (I) annealing at 950 °C for 24 h in air medium conditions and (II) annealing at 500 °C during 5 h under the oxygen annealing ambient. The standard measurement methods such as powder X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, temperature-dependent electrical resistance, and Vickers hardness measurements are performed for the characterization of materials. It is found that the samples prepared at SSR route present much more superior characteristic features as compared to those fabricated at SG technique, being one of the most striking points deduced this work. In more detail, every material prepared crystallizes in the orthorhombic symmetry and exhibits the superconducting nature but considerable decrement in the critical transition temperatures. The onset and offset transition temperatures are noted to decrease regularly from 92.96 K (92.28 K) to 90.20 K (83.59 K); and 90.05 K (90.03 K) to 45.97 K (30.49 K) for the materials prepared by the SSR (SG) route. Similarly, the variation in the lattice cell and average grain size parameters confirm that the Co/Cu substitution damages Y-123 superconducting phase. Additionally, the Co/Cu partial replacement mechanism leads to increase significantly the Vickers hardness results. To sum up, the Co/Cu partial substitution (produced by either SSR or SG method) is plowed to improve the fundamental characteristic features for new, novel, and feasible market application areas of Y-123 cuprate ceramics in the universe economy.
Keywords: Ca; Bi-2212 System; Y-123 Ceramics; Transport-Properties; Microhardness; Phase; Nanoparticles; Ybco Bulk Superconductors; Microstructure; Substitution; 7. Clean energy; 8. Economic growth